Evaluation of Dicumyl Peroxide as a Coupling Agent in Thermoplastic Starch and BioPBS Composites (2024)
To address plastic pollution from fossil fuel polymers, biodegradable alternatives like starch and polybutylene succinate (PBS) are proposed. However, starch is hydrophilic, while PBS and PBSA are hydrophobic. This research investigates the use of dicumyl peroxide (DCP) and tartaric acid (TA) as coupling agents in blends of thermoplastic starch (TPS) and PBS/PBSA, with glycerol as a plasticizer. Different weight/weight compositions of DCP and TA were added to blends in an internal mixer and subsequently compressed molded into films. DCP enhances tensile strength and ductility but increases torque and processing temperature. FTIR analysis show only a physical blend of components and no evidence of chemical interaction. TA reduces torque and tensile strength but increases ductility, with FTIR indicating that TA does not esterify starch but may form new bonds in the PBS carbonyl groups. SEM shows better compatibility in the blends.